Coupling between criticality and gelation in "sticky" spheres: a structural analysis. Issue 27 (29th May 2018) - Richard, David; Hallett, James; Speck, Thomas; Royall, C. Patrick
Abstract : We combine experiments and simulations to study the link between criticality and gelation in sticky spheres. Abstract : We combine experiments and simulations to study the link between criticality and gelation in sticky spheres. We employ confocal microscopy to image colloid–polymer mixtures and Monte Carlo simulations of the square-well (SW) potential as a reference model. To this end, we map our experimental samples onto the SW model. We find an excellent structural agreement between experiments and simulations, both for locally favored structures at the single particle level and large-scale fluctuations at criticality. We follow in detail the rapid structural change in the critical fluid when approaching the gas–liquid binodal and highlight the role of critical density fluctuations for this structural crossover. Our results link the arrested spinodal decomposition to long-lived energetically favored structures, which grow even away from the binodal due to the critical scaling of the bulk correlation length and static susceptibility.